Assay for enterotoxigenic Escherichia coli heat-stable toxin b in rats and mice. - Whipp, S C (1990)
The Escherichia coli heat-stable enterotoxin STb is the most prevalent toxin associated with diarrheagenic isolates of porcine origin. This report demonstrates that when endogenous protease activity was blocked with soybean trypsin inhibitor, STb evoked a dose-dependent secretory response in infant mice and jejunal loops of rats. Infant mice were much less sensitive to STb than rats were. The response of rat jejunal loops to STb was linearly related to the log of the dose of STb through 10 twofold dilutions. The anterior 25% of the jejunum was less sensitive than was the remainder of the gut. An incubation period of 2.5 h provided a maximal response. The linear response to STb in rats could be used as a bioassay.